2009
DOI: 10.1007/s11065-009-9097-y
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Remediation in Schizophrenia

Abstract: Cognitive deficits are routinely evident in schizophrenia, and are of sufficient magnitude to influence functional outcomes in work, social functioning and illness management. Cognitive remediation is an evidenced-based non-pharmacological treatment for the neurocognitive deficits seen in schizophrenia. Narrowly defined, cognitive remediation is a set of cognitive drills or compensatory interventions designed to enhance cognitive functioning, but from the vantage of the psychiatric rehabilitation field, cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
154
2
15

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(180 citation statements)
references
References 85 publications
4
154
2
15
Order By: Relevance
“…This suggestion is consistent with the work of Medalia and others, who have argued for a contextualized approach to rehabilitation that maximizes internal motivation. 235,236 Lastly, if the literature continues to support the crucial importance of individual differences in the degree to which schizophrenia have deficits in these different processes, this may suggest a basis for more individually tailored treatment approaches.…”
Section: Summary Suggestions For Future Research and Significancementioning
confidence: 99%
“…This suggestion is consistent with the work of Medalia and others, who have argued for a contextualized approach to rehabilitation that maximizes internal motivation. 235,236 Lastly, if the literature continues to support the crucial importance of individual differences in the degree to which schizophrenia have deficits in these different processes, this may suggest a basis for more individually tailored treatment approaches.…”
Section: Summary Suggestions For Future Research and Significancementioning
confidence: 99%
“…A number of studies involving antipsychotic treatments, behavior therapy and rehabilitation are present. Trials of medication have met with little success, potentially requiring exploration of non-drug treatment [115]. Antipsychotic effects on cognition and pharmacological augmentation as a cognitive enhancement strategy have met with limited success.…”
Section: Neurocognitive Function and Schizophreniamentioning
confidence: 99%
“…Also, these remediation effects are durable up to at least 6 months after the interventions are withdrawn [168]. Finally, and most importantly, these neuropsychological gains translate to improvements in real-world activities [169][170][171]. Similarily, cogni tive remediation programmes address prominent, complementary functional domains such as social cognition -and studies have furthermore observed beneficial effects on functional outcome measures in patient's posttreatment [172,173].…”
Section: Alternatives For Use Of Ce-drugsmentioning
confidence: 99%